Evaluation of bearing designs under the influence of electrical load - Kock, Ho Cheong (Nanyang Technological University, 2023)
As power electronics become commonly adopted in today’s industry, the frequency of motor drive system breaking down has increased which causes unnecessary operational downtime and results in monetary losses for companies. Hence, an in-depth investigation was carried out to determine the underlying factors of this problem. Previous studies have also discovered that the accelerated rate of bearing degradation was caused by the harmful bearing currents that were circulating in the machine. Furthermore, various existing monitoring and mitigation measures in improving the bearing performance were discussed. For this research study, the non-insulated bearing was tested to evaluate its effectiveness in reducing the rate of bearing degradation over time.